2007
DOI: 10.1111/j.1540-8191.2007.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Reductive Annuloplasty of the Mitral and Tricuspid Valves in Patients With End-Stage Ischemic Dilated Cardiomyopathy

Abstract: Reductive annuloplasty of mitral and tricuspid orifices performed at the time of myocardial revascularization could be beneficial in selective patients with ischemic dilated cardiomyopathy. Results indicate that this method should not be recognized as a valve repair, but ventricular repair procedure also.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…CABG has been associated with a perioperative stroke rate of 1-5% and the predisposing factors are consistent with the risk factors for perioperative stroke following MV procedures [2] . A subgroup analysis of 4 studies [5][6][7][8] A few limitations are to be addressed in our study. The final list of studies analyzed gathered from different sources and locations can differ in their guidelines for MV procedures and postoperative neurological assessment and follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CABG has been associated with a perioperative stroke rate of 1-5% and the predisposing factors are consistent with the risk factors for perioperative stroke following MV procedures [2] . A subgroup analysis of 4 studies [5][6][7][8] A few limitations are to be addressed in our study. The final list of studies analyzed gathered from different sources and locations can differ in their guidelines for MV procedures and postoperative neurological assessment and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Four primary studies with a sample size of 389 patients were analyzed [5][6][7][8] . A perioperative stroke rate of 2.05% (8/389) and 30-day mortality rate of 6.68% (23/389) were obtained.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…We believe that this approach is appropriate for patients with ischemic MR and also for patients with functional MR secondary to dilated cardiomyopathy (ischemic and nonischemic). Radovanovic et al (56,57) reported good results with systematic MV and TV annuloplasty in relatively young patients (mean age 50 to 55 years) with ischemic and nonischemic dilated cardiomyopathy, but his studies were nonrandomized. Early TV repair before the occurrence of irreversible RV dysfunction is probably also appropriate in patients with isolated TR secondary to TA dilation without left-sided heart disease (58).…”
mentioning
confidence: 97%
“…Myocardial revascularization was successfully achieved with triple bypass using left internal mammary artery to D 1 , and double venous CABG to RIM and CxOM 1 territory. By mini transseptal approach, modified stitch annuloplasty of mitral and tricuspid valves was performed in addition to myocardial revascularization 3 . Postoperative course of the patient was uneventful.…”
Section: Case Presentationmentioning
confidence: 99%
“…2 End-stage coronary artery disease is usually complicated with heart remodeling and functional mitral and tricuspid regurgitation. 3 In this report we present clinical findings and outcome in redo surgery 15 years after multiple coronary endarterectomies, complicated overtime with low ejection fraction (EF) and mitral and tricuspid insufficiency.…”
mentioning
confidence: 99%